5p+3=3(3p-5)

Simple and best practice solution for 5p+3=3(3p-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5p+3=3(3p-5) equation:


Simplifying
5p + 3 = 3(3p + -5)

Reorder the terms:
3 + 5p = 3(3p + -5)

Reorder the terms:
3 + 5p = 3(-5 + 3p)
3 + 5p = (-5 * 3 + 3p * 3)
3 + 5p = (-15 + 9p)

Solving
3 + 5p = -15 + 9p

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '-9p' to each side of the equation.
3 + 5p + -9p = -15 + 9p + -9p

Combine like terms: 5p + -9p = -4p
3 + -4p = -15 + 9p + -9p

Combine like terms: 9p + -9p = 0
3 + -4p = -15 + 0
3 + -4p = -15

Add '-3' to each side of the equation.
3 + -3 + -4p = -15 + -3

Combine like terms: 3 + -3 = 0
0 + -4p = -15 + -3
-4p = -15 + -3

Combine like terms: -15 + -3 = -18
-4p = -18

Divide each side by '-4'.
p = 4.5

Simplifying
p = 4.5

See similar equations:

| 2n+59=-4-5n | | -16+5n=-7-6+8n | | -3y/-3=25/-3 | | 7=1/2(-m-5) | | (1-4p)/50.2 | | 24=15-(4z-3) | | 21=-6m+39 | | 5k-6=-31 | | 4-3[2-(4y-5)]= | | -4(2x-3)=-8n-20 | | 7x^2-19x-8= | | 2x+33=162 | | 21/6/4 | | 81x+9y=72 | | 5(r+9)-2(-1-r)=1 | | 11.4=-14.2+4u | | 6x^2+2x=1 | | -4x+9x=3 | | -10=y/3-4 | | 33=172-u | | 56*x/7 | | -y+25=160 | | 141-x=201 | | -1/2*-1/4= | | 3x-20/2 | | 3+5+12+12=97 | | w/3-17=9 | | 7h+5-6=14 | | -21=-7w | | 2/3*3/2 | | 7/8u=21 | | 3b+5d=0 |

Equations solver categories